Risk management implementation for sustainable development of Romanian SMEs: A fuzzy approach - Carmen Ciocoiu; Adina Liliana Prioteasa; Sofia Elena Colesca (Amfiteatru Economic Journal, 2020)
Small and medium-sized enterprises (SMEs) are recognized for their major contribution to the economic development of any country. In Romania, SMEs represent 99.7% of all organizations and employ approximately 66% of all nationally registered employees, percentages approximately equal to those recorded in the European Union. However, the productivity of Romanian SMEs is quite low, feeling very strong any influence from the external environment. Risk management is increasingly considered a tool that can contribute to the sustainable development of SMEs. The implementation of a risk management system is a complex process, influenced by many factors. In this context, the objective of the present article is to analyze the determinants of behavior towards the implementation of risk management in Romanian SMEs. The data for the analysis were obtained through a questionnaire addressed to SMEs and processed by a fuzzy model. The results revealed two essential ideas: (1) the determinants of SMEs behavior towards risk management implementation are: stakeholders' requirements, training in risk management, the existence of a leader for the implementation and attitude towards risk; (2) attitude toward risk is influenced by the business lifespan and awareness of the importance of risk management.
Keywords: C02; D81; L21; M10; 330; small and medium-sized enterprises; integrated risk management; fuzzy approach; attitude towards risk; behavior; sustainable development